2021
DOI: 10.1002/cmdc.202000841
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors Targeting STAT5 Signaling in Myeloid Leukemias: New Tetrahydroquinoline Derivatives with Improved Antileukemic Potential

Abstract: Signal transducers and activators of transcription 5A and 5B (STAT5A and STAT5B) are two closely related STAT family members that are crucial downstream effectors of tyrosine kinase oncoproteins such as FLT3‐ITD in acute myeloid leukemia (AML) and BCR‐ABL in chronic myeloid leukemia (CML). We recently developed and reported the synthesis of a first molecule called 17 f that selectively inhibits STAT5 signaling in myeloid leukemia cells and overcomes their resistance to chemotherapeutic agents. To improve the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…Upregulation of cryptotanshinone on the expression of p-STAT5 supported protection against ischemic stroke ( Zhu et al, 2021 ), whereas the inhibitory effect of cryptotanshinone effectively antagonized chronic myelocytic leukemia (CML) ( Dong et al, 2018 ). Additionally, tetrahydroquinoline derivatives ( Polomski et al, 2021 ) and taxodione ( Uchihara et al, 2018 ) antagonized chronic myelocytic leukemia by inhibiting activation of STAT5 signaling. Moreover, silibinin ( Rugamba et al, 2021 ), naringenin ( Niu et al, 2018 ), xanthoplanine ( Shi et al, 2020 ), and menthol ( Suzuki et al, 2020 ) exhibited the biological potential of NSCLC, autoimmune inflammatory disorders, and arterial inflammation through inhibiting STAT5 signaling.…”
Section: Traditional Chinese Medicines or Herbs Or Natural Compounds ...mentioning
confidence: 99%
“…Upregulation of cryptotanshinone on the expression of p-STAT5 supported protection against ischemic stroke ( Zhu et al, 2021 ), whereas the inhibitory effect of cryptotanshinone effectively antagonized chronic myelocytic leukemia (CML) ( Dong et al, 2018 ). Additionally, tetrahydroquinoline derivatives ( Polomski et al, 2021 ) and taxodione ( Uchihara et al, 2018 ) antagonized chronic myelocytic leukemia by inhibiting activation of STAT5 signaling. Moreover, silibinin ( Rugamba et al, 2021 ), naringenin ( Niu et al, 2018 ), xanthoplanine ( Shi et al, 2020 ), and menthol ( Suzuki et al, 2020 ) exhibited the biological potential of NSCLC, autoimmune inflammatory disorders, and arterial inflammation through inhibiting STAT5 signaling.…”
Section: Traditional Chinese Medicines or Herbs Or Natural Compounds ...mentioning
confidence: 99%
“…Regarding dihydroquinolin-2-ones, several reports were found where N- aryl acrylamide substrates were submitted to Friedel-Crafts alkylation reactions where the Lewis acid AlCl 3 should be used under anhydrous conditions. [33][34][35][36] Other methodologies to obtain dihydroquinolin-2-ones with the same kind of olefinic substrate include photocycloaddition reactions catalyzed by an iridium organometallic complex with a reaction time of 48 h, [37] and an anti-Markovnikov hydroarylation of N-(2-bromophenyl)-N-methylmethacrylamide with the participation of Pd and Cu/ B 2 pin 2, under anhydrous conditions that takes 12 h. [38] Furthermore, metal-free radical cyclization employing persulfates, peroxides, iodic acid and different sources of radicals (azide, cycloalkanol, nitro, N-hydroxyphthalimide and α-diketones) have been used for the synthesis of oxindoles and dihydroquinolin-2-ones, also requiring long reaction times. [39][40][41][42][43][44] Despite the relevant synthetic contributions for the generation of oxindole and dihydroquinolin-2-ones, fast metal-free methodologies remain unknown in the literature , and thus relies on our findings (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that the installation/construction of oxindole and dihydroquinolin‐2‐one cores mostly rely on ring‐closing strategies that usually depend on methodologies catalyzed by transition metals that require long reaction times (Scheme 1 A) [25–38] . For example, oxindoles can be prepared from N ‐aryl acrylamides, through hydroarylation, where the latest methodologies involving reductive Heck coupling reactions are applied [27,28] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations